2020
DOI: 10.1002/term.2998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of keratin biomaterial containing silver nanoparticles as a potential wound dressing in full‐thickness skin wound model in diabetic mice

Abstract: Keratin is a cytoskeletal scaffolding protein essential for wound healing and tissue recovery. The aim of the study was to evaluate the potential role of insoluble fur keratin‐derived powder containing silver nanoparticles (FKDP‐AgNP) in the allogenic full‐thickness surgical skin wound model in diabetic mice. The scanning electron microscopy image evidenced that the keratin surface is covered by a single layer of silver nanoparticles. Data obtained from dynamic light scattering and micellar electrokinetic chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…is was related to the lack of moisture on the surface of the wound caused to generate some damage in the regenerated tissues at the change of gauze bandage. For the sample covered with PU/F nanofibers, better healing (higher wound closure percentage) was observed due to the higher absorption ability of PU/F wound dressing in comparison with gauze bandage that resulted in taking up wound exudates and providing a moist wound healing environment [53]. Also, relatively hindering property of the prepared scaffold from the penetration of bacteria into the wound surface can be another reason for higher efficiency of PU/F compared to gauze bandage.…”
Section: Wound Healing and Histological Examinationmentioning
confidence: 99%
“…is was related to the lack of moisture on the surface of the wound caused to generate some damage in the regenerated tissues at the change of gauze bandage. For the sample covered with PU/F nanofibers, better healing (higher wound closure percentage) was observed due to the higher absorption ability of PU/F wound dressing in comparison with gauze bandage that resulted in taking up wound exudates and providing a moist wound healing environment [53]. Also, relatively hindering property of the prepared scaffold from the penetration of bacteria into the wound surface can be another reason for higher efficiency of PU/F compared to gauze bandage.…”
Section: Wound Healing and Histological Examinationmentioning
confidence: 99%
“…Although the presence of the inflammatory cells is more preferable during the healing process, the continuing of this process leads to produce scar tissue. In contrast, in control wounds, neutrophils predominated at this time point with lymphocytes (Konop et al, 2020). On the 21st day, epithelialization expanded greater and faster in the Trial 2 groups compared to the control and Trial 1 groups, and had covered the surface of wound, which can be due to participation of mesenchymal cells and their ability in control of inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…The regeneration of epidermis and dermis layers starts with cell migration of wound edges into the wound, and the histological appearance of the wound tissue was completed on Day 21. H&E staining and counting of leukocytes (lymphocytes and neutrophils), new blood vessels and fibroblasts were evaluated at three time point after scaffold implantation and was shown in Figure S2 and S3 and Table S2 ( Konop et al, 2020). These results revealed that…”
mentioning
confidence: 86%
“…Keratin biomaterials soluble or insoluble are promising candidates in the field of wound dressing materials due to their tissue biocompatibility and ability to support cell growth [ 8 , 20 ]. Moreover, several studies have shown that insoluble keratin enhances tissue recovery and promotes macrophages infiltration during the skin repair process in healthy and diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, keratin contains the binding motif sequences RGD (Arg-Gly-Asp) and LVD (Leu-Asp-Val), which are also found in extracellular matrix proteins such as fibronectin, laminin, collagens, among others [ 5 , 6 ]. The heterogeneous structure of the keratin scaffolds facilitates cell adhesion and allows surface modification with analgesic or antibacterial agents [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%